Study on the shear concentration in high‐rise buildings with transfer structure and its effects on seismic performance. (17th April 2022) - Jin, Chenhua; Wu, Chang; Pan, Zuanfeng; Meng, Shaoping
Summary: The architectural complexity and multifunctional requirements for modern high‐rise buildings usually lead to the utilization of combined structural systems, which typically consists of shear walls in higher zones while frames–core walls in lower zones. To fulfill reasonable load transfer between the different structural forms, transfer structures are commonly introduced in high‐rise buildings. However, the abrupt conversion in structural form usually causes shear concentration effect in the exterior walls just above the transfer structure, which is particularly vulnerable to seismic loading. In this paper, finite element models based on several types of practical high‐rise buildings were presented and analyzed to simulate the shear concentration effect in exterior walls. It was verified that the assumption of infinite stiffness in transfer structures will lead to underestimation of the shear concentration effect. The local deformations of transfer structures were demonstrated to be a key factor to scale the shear concentration. A scale factor of the shear concentration in the shear walls ( SCSF ) which can measure the intensity of shear concentration was defined. Parametric studies were carried out to provide insight on the influence factors of shear concentration. The results indicated that the SCSF only related to the difference between the rotation of external walls and center walls. Based on time‐history analysis, the influence of SCSF on the seismic performance of high‐rise buildings with transfer structures was studied. The results indicated that decreasing of SCSF can control the local damage caused by shear concentration, thereby improving the seismic performance of the structure.